The Effect of A Combination of Commercial Feed And Maggots On Protein Retention In Freshwater Lobsters (Cherax quadricarinatus) - Ardi Eko Mulyawan; Andi Alham Mulia; Nursyahran Nursyahran (Indonesian Journal of Coastal and Marine Studies, 2025)
This study aims to determine the effect of a combination of commercial feed and maggots on protein retention in freshwater lobsters (Cherax quadricarinatus). This study was conducted in July - August 2024. The samples that have been taken were then taken to the laboratory for analysis and then ANOVA tests were carried out to determine the differences. The results of the study showed that the results of the ANOVA analysis showed a significant difference in protein levels between the treatments tested. Based on the ANOVA output, the calculated F value was 150.106 with a significance value (Sig) of 0.000, which is smaller than 0.05, so it can be concluded that there is a significant difference between the treatment groups tested. In a follow-up test using Tukey HSD, comparisons between groups showed that each treatment had a significant average difference. For example, the average difference between P0 and P1 was -1.81000, which has a significance value of 0.001, which means the difference is significant. Similarly, comparisons between P0 and P2, P0 and P3, P1 and P2, P1 and P3, and P2 and P3 all showed significant differences (p-value <0.05). Furthermore, analysis with subsets for alpha = 0.05 showed that P2 had the highest average protein content (24.2733), followed by P3 (22.9633), P1 (20.4533), and P0 (18.6433). These groups were divided into four homogeneous subsets, indicating that the P2 treatment was significantly higher compared to the other treatments. Overall, the results of the ANOVA and Tukey HSD test showed that different treatments significantly affected protein levels, with the P2 treatment showing the highest protein content.